Pemanfaatan Limbah Beton Sebagai Pengganti Agregat Kasar Dengan Penambahan Zat Additive Beton Mix Terhadap Nilai Kuat Tekan Beton - Ansar, Zulfitrah; Mustakim, Mustakim; Fadly, Imam (Universitas Sulawesi Tenggara, 2024)
Utilization of concrete waste as an additional material for making concrete. And this research also adds chemical additives to the concrete mix using recycled coarse aggregate which is expected to increase the strength of the concrete. This research aims to determine the effect of adding concrete waste on the compressive strength of concrete due to variations in adding additives (Concrete Mix). and Knowing the comparison results of each substitute mixture of pure coarse aggregate with recycled coarse aggregate added with additives (Concrete Mix). This research method uses an experimental research method by comparing 4 (four) variations of the mixture to determine the compressive strength of concrete with a design compressive strength of 25 MPa. The results of the research show that each variation with a cylindrical specimen of 300mm x 150mm with a soaking age of 28 days, variations normal concrete with an average compressive strength of 25.38 MPa, a variation of 25% waste concrete with an average compressive strength of 21.89 MPa, a variation of waste concrete + 400ml mixed concrete with an average compressive strength of 25.48 MPa and a variation of waste concrete + mixed concrete 600ml with an average compressive strength of 28.31 MPa. So it can be concluded that the use of 25% concrete waste does not meet the planned compressive strength and cannot be used in construction, whereas by adding 400ml and 600ml mixed concrete additives, the maximum compressive strength is obtained and is suitable for use in construction.